Evaluation of a 36 Gy elective node irradiation dose in anal cancer. Issue 2 (August 2015) - Lépinoy, Alexis; Lescut, Nicolas; Puyraveau, Marc; Caubet, Matthieu; Boustani, Jihane; Lakkis, Zaher; Fantoli, Michel; Buffet-Miny, Joelle; Kim, Stefano; Bednarek, Coraline; Maingon, Philippe; Créhange, Gilles; et al.
Abstract: Purpose: To retrospectively analyze the efficacy of 36 Gy of elective node irradiation and report patterns of recurrence in patients with anal cancer treated by chemoradiation with the same radiotherapy (RT) treatment scheme. Methods and materials: Between January1996 and December 2013, 142 patients with anal squamous cell cancer were scheduled to receive a dose of 36 Gy of elective node irradiation (ENI) to the inguinal area and whole pelvis over 4 weeks followed after a 2-week gap by a boost dose of 23.4 Gy over 17 days to the macroscopic disease. Mitomycin C combined with fluorouracil, capecitabin or cisplatin was given at day 1 of each sequence of RT. Results: Disease stages were I: 3, II: 78, IIIA : 23, IIIB : 38. Compliance rates were 97.2% with RT and 87.9% with chemotherapy. After a median follow up of 48 months [3.6–192], estimated 5-year overall survival and colostomy-free survival were 75.4% and 85.3% respectively. Eleven patients (7.7%) never achieved a complete response, 15 had a local component of recurrence and 5 a regional one. One patient had failure in the common iliac node area outside the treatment fields. The inguinal control rate was 98.5%. The 5-year tumor and nodal control rates were 81.5% and 96.0%, respectively. Conclusion: Chemoradiation with a dose of 36 Gy ENI achieved excellent nodal control. However, it is necessary to improve the 5-year control rate of the primary tumor. Omitting the gap and using additional doses per fraction or hyper-fractionation are to be explored.